Chlorination of Taurine by Human Neutrophils: EVIDENCE FOR HYPOCHLOROUS ACID GENERATION - Weiss, Stephen J. (1982)
The model hydrogen peroxide-myeloperoxidase-chloride system is capable of generating the powerful oxidant hypochlorous acid, which can be quantitated by trapping the generated species with the β-amino acid, taurine. The resultant stable product, taurine chloramine, can be quantitated by its ability to oxidize the sulfhydryl compound, 5-thio-2-nitro-benzoic acid to the disulfide, 5,5′-dithiobis(2-nitroben-zoic acid) or to oxidize iodide to iodine. Using this system, purified myeloperoxidase in the presence of chloride and taurine converted stoichiometric quantities of hydrogen peroxide to taurine chloramine. Chloramine generation was absolutely dependent on hydrogen peroxide, myeloperoxidase, and chloride and could be inhibited by catalase, myeloperoxidase inhibitors, or chloride-free conditions. In the presence of taurine, intact human neutrophils stimulated with either phorbol myristate acetate or opsonized zymosan particles generated a stable species capable of oxidizing 5-thio-2-nitrobenzoic acid or iodide. Resting cells did not form this species. The oxidant formed by the stimulated neutrophils was identified as taurine chloramine by both ultraviolet spectrophotometry and electrophoresis. Taurine chloramine formation by the neutrophil was dependent on the taurine concentration, time, and cell number. Neutrophil-dependent chloramine generation was inhibited by catalase, the myeloperoxidase inhibitors, azide, cyanide, or aminotriazole and by chloride-free conditions, but not by superoxide dismutase or hydroxyl radical scavengers. Thus, it appears that stimulated human neutrophils can utilize the hydrogen peroxide-myeloperoxidase-chloride system to generate taurine chloramine. Based on the demonstrated ability of the myeloperoxidase system to generate free hypochlorous acid we conclude that neutrophils chlorinate taurine by producing this powerful oxidant. The biologic reactivity and cytotoxic potential of hypochlorous acid and its chloramine derivatives suggest that these oxidants play an important role in the inflammatory response and host defense.